AB0752 Consensus statement on the use of methotrexate in psoriatic arthritis patients. (15th June 2017) - Tornero, J; Loza, E; Cañete, JDD
Abstract : Background: Methotrexate (MTX) is the cornerstone in rheumatic diseases, including psoriatic arthritis (PsA), but the complexity of PsA and the paucity of randomised controlled studies and strategic trials need a clear analysis. Objectives: To develop recommendations for the management of MTX in PsA (musculoskeletal manifestations) based on best evidence and experience Methods: The coordinators formulated 14 questions about MTX use (indications, efficacy, safety) in patients with PsA. A systematic literature review was performed to answer these questions. Using this information, inclusion and exclusion criteria were stablished as well as the search strategies (Medline, Embase and the Cochrane Library), that were designed by an expert librarian. Two different reviewers selected the articles, first by title and abstract, then by detailed review, and collected data independently. Evidence tables were produced. With this evidence the coordinators proposed 12 preliminary recommendations that will be discussed and voted in a nominal group of expert meeting. The level of evidence and grade of recommendation will be defined using the Oxford Center for Evidence Based Medicine. Agreement will be stablished if at least 80% of the experts voted yes (yes/no). Results: A total of 12 preliminary recommendations on the use of MTX in PsA were proposed (see table). Conclusions: This document aims to help to answer usual clinical questions and facilitate decision making when treating PsA patients with MTX. Disclosure of Interest: J. Tornero: None declared, E. Loza Grant/research support from: Abbie, Pfizer, Roche, Gebro, BMS, UCB, J. Cañete: None declared